Preimplantation genetic testing for aneuploidy: a pragmatic, multicenter randomized clinical trial of single frozen euploid embryo transfer versus selection by morphology alone. (April 2019) - Munné, Santiago; Kaplan, Brian; Frattarelli, John L.; Gysler, Mathias; Child, Tim; Nakhuda, Gary; Shamma, F. Nicholas; Silverberg, Kaylen; Kalista, Tasha; Oliver, Kelly; Handyside, Alan H.; Katz-Jaffe, Mandy; et al.
Abstract : Using comprehensive screening techniques, several small and single-center RCTs have shown that Preimplantation genetic testing for aneuploidy (PGT-A) increases pregnancy and live birth rates per transfer compared to morphology alone. These studies were mostly performed by very experienced IVF and PGT laboratories. Next generation sequencing (NGS) based PGT-A has the advantage over previous techniques of having a larger dynamic range and resolution allowing the detection of mosaicism in the 20-80% range and therefore allowing for better selection of embryos. A new RCT study was designed to test if NGS applied in regular fertility centers in a multicenter setting would improve ART outcomes. The RCT, called STAR, was multicentre, pragmatic RCT, involving 662 women ages 25-40 undergoing IVF with at least two blastocyst biopsied, no history of RPL or RIF. The patients were randomly assigned to a SET with either PGT-A or morphology alone. Only euploid embryos were transferred to the PGT-A arm and mosaic embryos were not replaced. The primary outcome was a clinical pregnancy at 20 weeks gestation following a single embryo transfer. Clinical pregnancy occurred in 137/274 (50%) of transfers with PGT-A and in 144/314 (46%) with morphology alone. However, post hoc analysis of pregnancy/live birth rates in women aged between 25- 34 and 35-40 years was 49 and 51% (not significant) and 51% and 37% ( p =0.035), respectively. Overall clinical pregnancy and live birth rates were similar between groups, however, there was a significant increase in live birth in women ages 35-40 years when PGT-A was used for embryo selection. There results resemble those reported by SART in 2014. Some reasons for the lack of improvement in the young age group are the exclusion of RIF and RPL patients, the rule of not replacing mosaic embryos when no euploid ones were available, and probably sub-optimal biopsy or transfer techniques in some clinics in this real-world study.